OPTIMISASI PANJANG LATERAL SUMUR HORIZONTAL PADA RESERVOIR HETEROGEN DENGAN MEMPERTIMBANGKAN KEHILANGAN TEKANAN AKIBAT FRIKSI PADA ALIRAN MULTI FASA - Rahman, Fatkhur
Advanced in drilling technology have focused oil industry’s attention on importance of horizontal -well, because it gives more advantages. In cases with long wells, pressure drop due to friction might be comparable with drawdown. Ignoring friction could lead to unrealistic higher rates estimation so results higher optimum length. Several studies had been conducted to optimize the length by considering friction. The studies were generated for homogenous reservoir and single-phase flow. Final result of optimization is revenue versus lateral length plot so that optimum length can be noticed. Similar study will be developed for heterogeneous reservoir and multiphase flow by using EclipseTM and model from SPE 29110. The optimization is done for three different wellhead locations. Variations of well properties are not investigated, because the optimum lateral length only depends on permeability and porosity distribution. All scenarios results similar optimum lateral length and NPV.